Protection of Victims of Bullying Crimes in Traditional Crim-inal Law - Murshal Senjaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
In the customary law system, there is a pattern of punishment and prosecution which is more or less similar to the Islamic legal system, where the role of the victim's family is very important in determining whether or not the perpetrator will be prosecuted and punished. In customary law, legal settlements are carried out with an emphasis on togetherness or harmony. Settlement of criminal cases, especially bullying through customary law, is a process of resolving cases outside of court which consists of first, a mediation system with a consensus approach through deliberation. Second, the restorative justice system is a case resolution system with the aim of restoring the situation that arose for the victim so that a sense of brotherhood between each party is re-established. This system produces an agreement that is a win-win solution, guarantees the confidentiality of the parties' disputes, avoids delays caused by procedural and administrative matters, and resolves problems comprehensively together and while maintaining good relations. Thus, these customary sanctions do not provide legal protection and fulfillment of children's rights for children who are victims of sexual violence. In sexual crimes against children, children are positioned as victims who experience detrimental impacts, namely physical and psychological harm. Therefore, it is mandatory to be protected, not judged.